The different influences of the government and politicians on the international expansion of Chinese firms. Issue 5 (December 2018) - Noh, Grimm; Shin, Dongyoub
Abstract This paper examines the influences from the political sector on international expansion of Chinese firms. In analyzing the political sector, we distinguish between 'formal institutional influences from the government' and 'informal relational influences from elite politicians.' We argue that the government can pressure emerging-market firms to expand abroad despite the risk when outbound globalization is the national policy. However, networks with powerful politicians can discourage international expansion since sufficient domestic returns provided by the political connections can lead to lower motivation for internationalization. The governmental pressures toward internationalization can be moderated by firm size and relational networks with powerful politicians.